Procesi učenja z vidika učnih težav učencev pri matematiki - Žakelj, Amalija (Revija za elementarno izobraževanje, 2014)
Processes of Learning with Regard to Students’ Learning Difficulties in Mathematics. In the introduction, we write about the process of learning mathematics: the development of mathematical concepts, numerical and spatial imagery on reading and understanding of texts, etc. The central part of the paper is devoted to the study, in which we find that identifying the learning processes associated with learning difficulties of students in mathematics, is not statistically significantly different between primary school teachers and teachers of mathematics. Both groups expose the development of numerical concepts, logical reasoning, and reading and understanding the text as the ones with which difficulties in learning mathematics appear the most frequently. All the processes of learning that the teachers assessed as the ones that represent the greatest barriers to learning have a fairly uniform average estimates of the degree of complexity, ranging from 2.6 to 2.8, which is very close to the estimate makes learning very difficult.
Keywords: mathematics; learning processes; development of numeric conception; reading and text comprehension; barriers to learning mathematics